PELUANG USAHA DALAM MENINGKATKAN EKONOMI KELUARGA PEDAGANG WARUNG DI PERUMAHAN KARYAWAN PT. ASTRA AGRO LESTARI KECAMATAN KOTO GASIB KABUPATEN SIAK - Situmorang, Mey Fitri; ", Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
There are some strategies should be considered and done by sellers to maintain a sale business such as customer satisfaction strategy, marketplace strategy, product strategy, price strategy, distribution strategy and marketing strategy in competition world. These strategies are done by sellers to maintain their stall business to increase their income. Yet the arguments have to be proven through a research to get an accurate answer. The questions of the research are 1) what kinds charakteristik by the sellers at the residence of PT Astra Agro Lestari and 2) how is the strategy implemented by the owners of stall around the residence of PT Astra Agro Lestari which is in desa Pangkalan Pisang, kecamatan Koto Gasib kabupaten Siak to keep selling. The population of the research is the sellers who sell at employee residence area of PT Astra Agro Lestari numbered 44 sellers. The technique of sampling used is purposive sampling with the sample is only 25 sellers who have sold for 5 years. The technique of collecting data is questionnaire. The data got of the research was descriptive quantitative. Generally, the result of the research found by the writer is there are some sellers who do not understand about strategies in selling, so it is expected to implement the strategies to maintain the selling business in gaining income and fulfilling family needs.Keywords : Seller, Strategy, Product